Public Policy and the Labor Market Adjustment of New Immigrants to Australia - Deborah A. Cobb-Clark (Institute for the Study of Labor (IZA), 2002)
Two separate cohorts of immigrants to Australia are compared in order to assess the potential role of immigrant selection criteria, labor market conditions, and income-support policy in facilitating the labor market adjustment of new arrivals. Although these two cohorts entered Australia only five years apart, their initial labor market outcomes varied dramatically. The results indicate that changes in immigration policy may have led to increased human capital endowments that in turn resulted in higher participation rates and reduced unemployment. At the same time, improvement in Australian labor market conditions and changes in income-support policy over the 1990s – which most likely altered the returns to human capital – were probably instrumental in reinforcing the effects of tighter immigrant selection criteria. As much as half of the fall in unemployment rates among women and one third the decline among men appears to have occurred as the result of changes in the returns to demographic and human capital characteristics.
Keywords: J1; J6; 330; immigrant; labor market assimilation; selection criteria; public policy; Einwanderung; Einwanderungsrecht; Sozialhilfe; Reform; Hochqualifizierte Arbeitskräfte; Arbeitsmarkt; Soziale Integration; Schätzung; Australien